Perencanaan Gedung Pusat Penjualan Alat Tulis Kantor dan Alat Peraga Pendidikan Dengan Penekanan Arsitektur Origami di Kota Samarinda - Malik, Adam; Wardhana, Wardhana; Riza, Ahmad (Kurva S : Jurnal Keilmuan dan Aplikasi Teknik Sipil, 2023)
Community activities of various groups ranging from civil servants, private employees, junior high school students and high school students, students who have a fairly high development potential in samarinda are the reason for the need for planning a building for selling office stationery and teaching aids Education. The purpose of the research is to plan the Office Stationery Sales Building and Educational Teaching Aid in Samarinda with the application of the Modular Origami architectural style, in addition to being a Office Stationery Sales Building and Educational Teaching Aids so that people can shop complete as needed such as pens, pencils, paper, desks. , chairs, bookcases, cupboards, for special store rooms, exact educational teaching aids such as chemistry, biology, and various kinds of analytical tools for all school laboratory needs.